Academic skills in children with autism spectrum disorders with monolingual or bilingual experience. (November 2019) - Vanegas, Sandra B
Background and aims: The academic development of children with autism spectrum disorders is important to investigate as it can provide opportunities for higher education, independent living, and successful employment in adulthood. Although educational data find that children with autism spectrum disorders can achieve similar levels of academic achievement in inclusive settings as neurotypical children, little is known about how children with diverse language experiences with autism spectrum disorders develop academically. Research on neurotypical, bilingual children finds that although many may lag behind their monolingual peers on measures of academic achievement, these gaps can be minimized with bilingual education programs. Within clinical practice, concerns are still raised about bilingual exposure in children with autism spectrum disorders, with assumptions and recommendations made to limit the language of exposure to minimize risks to development. To improve the evidence-base on bilingual experience in children with autism spectrum disorders, the present study will examine whether basic academic skills (i.e., word reading, numerical operations, spelling) vary as a function of language experience (i.e., monolingual vs. bilingual). Methods: The data presented in this study were based on medical records of children with autism spectrum disorders who visited a clinic in a large, urban city in the United States. Records were included for this study if children had information/data on language status, nonverbal cognition, and standardized scores for reading, math, and spelling on a standardized academic achievement test. The final sample included children with autism spectrum disorders with monolingual language experience ( n = 18) or bilingual language experience ( n = 13). Results: Repeated measures analysis of variance analyses found that children with autism spectrum disorders with monolingual experience had higher scores on word reading skills when compared to children with autism spectrum disorders with bilingual experience. However, a different pattern was found for numerical operations, with children with autism spectrum disorders with bilingual experience outperforming children with autism spectrum disorders with monolingual experience. No differences were found between groups on spelling skills. Conclusions: The preliminary findings suggest that bilingual language experience may be related to early literacy and math skills in children with autism spectrum disorders. It may be that word reading skills are slower to develop among children with autism spectrum disorders with bilingual experience due to the development of two linguistic profiles. Math skills may be enhanced in children with autism spectrum disorders with bilingual experience through the mediation of other cognitive skills (e.g., executive functioning). Implications: This preliminary study demonstrates that bilingual experience does not negatively affect the development of academic skills in children with autism spectrum disorders. Further exploration of how bilingual experience may benefit children with autism spectrum disorders is needed.